Literature Review: Strategi Pemasaran Marketing Mix Terhadap UMKM Lokal - Yasmin, Muhamad Adiala; Agata, Nindia Ellissa; Nauli, Anggi; Mauboy, Rafael Valentino (Jurnal Disrupsi Bisnis, 2024)
MSME (Micro, Small and Medium Enterprises) have an important and strategic role in economic growth, so there is a need for a marketing strategy to develop local MSMEs. Marketing mix is ​​a marketing strategy that emphasizes various factors known as the 7Ps. This research aims to discuss marketing mix strategies for local MSMEs through a literature review. The method used is qualitative with a literature review. This research data uses secondary data through online observation. The results of the research by drawing conclusions from several journal descriptions studied show that marketing strategies using a marketing mix can increase the effectiveness of MSMEs, such as increasing sales volume and increasing the competitiveness of MSMEs in the current era of intense competition.